IMPLEMENTATION OF PUBLIC-PRIVATE PARTNER-SHIP PROJECTS IN THE RUSSIAN ARCTIC - O. Bolshakova; V. Volkova; A. Surnova (Вестник университета)
The application of public-private partnership to stimulate the socio-economic development of the Arctic zone are considered. The importance of this task is determined by the fact that the reserves of natural resources located in the Arctic should provide the basis for the energy and economic security of the country. The comparative analysis of ways of realization of infrastructure projects on the basis of the state order and public - private partnership is carried out. The aspects of the influence of public-private partnership on the development of the region and increase its investment potential are discussed.